Sistem Ekonomi Islam Dalam Persepsi Tokoh Agama Desa Pagutan Kecamatan Batukliang Kabupaten Lombok Tengah - Dedi Riswandi; Mashur Mashur; Ahmad Sibawai (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2023)
Discussing about the Islamic Economic System turns out to be quite different. One of the reasons is because the Islamic economic system gives the main characteristics that are based on Islamic law, in contrast to the conventional economy which is based on the capitalist economic system or also called the secular economy. This research is field research. Researching the perceptions and opinions of religious leaders in the midst of society in general. Methods of collecting data by means of observation, interviews, questionnaires, and documentation. The data analysis is descriptive analysis where the data obtained is analyzed and then given an explanation and conclusion. The Islamic economic system seeks to fight the principles of usury, maysir and gharar which are the main principles in the application of the conventional economic system. In every conventional economic transaction, these three principles are always put forward. The impact of these practices then brings disaster in the social life of the community such as exploitation, unfair distribution of income and wealth, fading of the attitude of togetherness and brotherhood, the emergence of social problems and so on. The results of this research about the perceptions of religious leaders regarding the Islamic economic system can be used as the main basis for society in every action and economic practice.